The effect of development on employee career improvement in the Secretariat Office Region of Nias District - Waruwu, Sukaaro; Laoli, Victorinus (JURNAL MANAJEMEN MOTIVASI, 2018)
This study aims to determine the effect of development on employee careerimprovement at the Office of the Regional Secretariat of Nias Regency. The sample inthis research is by using random sampling. The analysis technique used is a simplelinear correlation analysis, simple linear regression analysis. The method used in thisresearch is a descriptive method with the quantitative approach that is the method inresearching the status of a group of people, an object, a set of condition or system ofthought or a class of events in the present. From the results of research conducted, it isobtained results that: Based on the results of hypothesis testing obtained that there issignificant influence between the development of employee career improvement atthe office of the district secretariat nias.